Wage versus efficient bargaining in a Cournot duopoly: A Preliminary Note on Welfare - Buccella, Domenico (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In a unionized Cournot duopoly with decentralized, firm-level bargaining, this note re-examines the endogenous equilibrium agendas (wage vs. efficient bargaining) that can arise under three different specifications of the timing of negotiations and the impact of the outcome of the bargaining process on social welfare. Given that explicit conflict of interest among the bargaining parties can arise in every timing specification, this note proposes, analyzes, and discusses some guiding principles for governments and public authorities interested in pursuing social welfare improvements.
Keywords: rokowania; płace; opieka społeczna